2016
DOI: 10.1120/jacmp.v17i6.6433
|View full text |Cite
|
Sign up to set email alerts
|

Deriving detector‐specific correction factors for rectangular small fields using a scintillator detector

Abstract: The goal of this study was to investigate small field output factors (OFs) for flattening filter‐free (FFF) beams on a dedicated stereotactic linear accelerator‐based system. From this data, the collimator exchange effect was quantified, and detector‐specific correction factors were generated. Output factors for 16 jaw‐collimated small fields (from 0.5 to 2 cm) were measured using five different detectors including an ion chamber (CC01), a stereotactic field diode (SFD), a diode detector (Edge), Gafchromic fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 34 publications
(52 reference statements)
1
27
0
Order By: Relevance
“…Therefore, the field output factor is simply a dose ratio or the ratio of detector readings multiplied by a Monte Carlo calculated correction factor, kQitalicclin,Qitalicmsrfitalicclin,fitalicmsr, which accounts for the difference between the detector response in the clinical and reference field; hence, in small field output factors calculation, these are determined using the equation below: Dw,QitalicclinfclinDw,Qitalicmsrfmsr=MQitalicclinfitalicclinMQitalicmsrfitalicmsrkQclin,Qmsrfclin,fmsrwhere MQclinfclin is the measured reading for a clinical field size, and MQmsrfmsr is the measured reading at a reference field size. The magnitude of kQitalicclin,Qitalicmsrfitalicclin,fitalicmsr varies widely depending on type of machine (source size), field size, depth of measurement, and more importantly detector design . Mistakes in accounting for these dependencies have produced radiation accidents that have serious consequences for patient care…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the field output factor is simply a dose ratio or the ratio of detector readings multiplied by a Monte Carlo calculated correction factor, kQitalicclin,Qitalicmsrfitalicclin,fitalicmsr, which accounts for the difference between the detector response in the clinical and reference field; hence, in small field output factors calculation, these are determined using the equation below: Dw,QitalicclinfclinDw,Qitalicmsrfmsr=MQitalicclinfitalicclinMQitalicmsrfitalicmsrkQclin,Qmsrfclin,fmsrwhere MQclinfclin is the measured reading for a clinical field size, and MQmsrfmsr is the measured reading at a reference field size. The magnitude of kQitalicclin,Qitalicmsrfitalicclin,fitalicmsr varies widely depending on type of machine (source size), field size, depth of measurement, and more importantly detector design . Mistakes in accounting for these dependencies have produced radiation accidents that have serious consequences for patient care…”
Section: Introductionmentioning
confidence: 99%
“…Response of detectors in small fields and the determination of detector‐specific output correction factors have been extensively investigated for a range of detectors by several research groups, using one of the following three techniques: (a) empirical approach, where uncorrected signal ratios were determined and compared to the field output factors determined with reference detectors, (b) numerical approach, where kQitalicclin,Qitalicreffitalicclin,fitalicref were determined with MC simulations, and (c) semi‐empirical approach which combines both, measurements and numerical/analytical calculations, and where kQitalicclin,Qitalicreffitalicclin,fitalicref were the most commonly determined through the comparison of measured uncorrected detector's signal ratios with MC calculated field output factors . There are advantages and disadvantages of each of these approaches .…”
Section: Introductionmentioning
confidence: 99%
“…There are many publications on the dosimetric characteristics of the PSD . Among which, several studies demonstrated that the PSD achieved similar dose response to other widely accepted benchmarks, such as Monte Carlo, Gafchromic films and diamond detectors . The PSD is thus chosen to be the benchmark in our study.…”
Section: Introductionmentioning
confidence: 99%